Metastatic Potential and Survival of Duodenal and Pancreatic Tumors in Multiple Endocrine Neoplasia Type 1: A GTE and AFCE Cohort Study (Groupe d'étude des Tumeurs Endocrines and Association Francophone de Chirurgie Endocrinienne). Issue 6 (December 2020) - Vinault, Sandrine; Mariet, Anne-Sophie; Le Bras, Maëlle; Mirallié, Eric; Cardot-Bauters, Catherine; Pattou, François; Ruszniewski, Philippe; Sauvanet, Alain; Chanson, Philippe; Baudin, Eric; Elias, Dominique; Menegaux, Fabrice; et al.
Abstract : Objective: To assess the distant metastatic potential of duodeno-pancreatic neuroendocrine tumors (DP-NETs) in patients with MEN1, according to functional status and size. Summary Background Data: DP-NETs, with their numerous lesions and endocrine secretion-related symptoms, continue to be a medical challenge; unfortunately they can become aggressive tumors associated with distant metastasis, shortening survival. The survival of patients with large nonfunctional DP-NETs is known to be poor, but the overall contribution of DP-NETs to metastatic spread is poorly known. Methods: The study population included patients with DP-NETs diagnosed after 1990 and followed in the MEN1 cohort of the Groupe d'étude des Tumeurs Endocrines (GTE). A multistate Markov piecewise constant intensities model was applied to separate the effects of prognostic factors on 1) metastasis, and 2) metastasis-free death or 3) death after appearance of metastases. Results: Among the 603 patients included, 39 had metastasis at diagnosis of DP-NET, 50 developed metastases during follow-up, and 69 died. The Markov model showed that Zollinger-Ellison-related tumors (regardless of tumor size and thymic tumor pejorative impact), large tumors over 2 cm, and age over 40 years were independently associated with an increased risk of metastases. Men, patients over 40 years old and patients with tumors larger than 2 cm, also had an increased risk of death once metastasis appeared. Conclusions: DP-NETs of 2 cm in size or more, regardless of the associated secretion, should be removed to prevent metastasis and increase survival. Surgery for gastrinoma remains debatable. Abstract : Supplemental Digital Content is available in the text